2021
DOI: 10.1590/1678-7757-2020-0998
|View full text |Cite
|
Sign up to set email alerts
|

The effect of solution and gel forms of sodium hypochlorite on postoperative pain: a randomized clinical trial

Abstract: The effect of solution and gel forms of sodium hypochlorite on postoperative pain: a randomized clinical trial Objectives: The aim of this study is to evaluate the effect of using gel and solution forms of NaOCI during the chemomechanical preparation of the root canals on postoperative pain at different time intervals. Methodology: 114 patients with mandibular molar teeth and symptomatic irreversible pulpitis were included in the study. All patients were divided into two groups based on the irrigant used durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 29 publications
0
18
0
Order By: Relevance
“…Studies have shown that the gel form of NaOCl may be advantageous in reducing postoperative pain. However, the effectiveness of gel form in disinfection and smear removal is inconclusive [1]. Previous studies have evaluated the impact of several NaOCl forms on root canal dentin's microhardness.…”
Section: International Journal Of Dental Materials 2024; 6 (1 )mentioning
confidence: 99%
See 4 more Smart Citations
“…Studies have shown that the gel form of NaOCl may be advantageous in reducing postoperative pain. However, the effectiveness of gel form in disinfection and smear removal is inconclusive [1]. Previous studies have evaluated the impact of several NaOCl forms on root canal dentin's microhardness.…”
Section: International Journal Of Dental Materials 2024; 6 (1 )mentioning
confidence: 99%
“…Moreover, a study by Karatas et al concluded that the NaOCl gel results in less postoperative pain than the NaOCl solution on day 1 of endodontic treatment [3]. Another survey by Ozlek et al showed that using the NaOCI gel form during root canal irrigation resulted in postoperative pain similar to that of the solution form [1]. Nonetheless, the comparison between different concentrations and formulations of NaOCl in root canal treatment has not been systematically assessed.…”
Section: International Journal Of Dental Materials 2024; 6 (1 )mentioning
confidence: 99%
See 3 more Smart Citations